Driving Excellence: The Effect of Work Discipline and Incentive Programs on Employee Performance - Songyanan, Evalyn Margareth Carolina; Kasbuntoro, Kasbuntoro (Human Capital and Organizations, 2024)
This research evaluates the influence of work discipline and providing incentives on employee performance at PT. TOA Galva Industries, especially in the Speaker Department 1. We use correlation regression, determination, t-test, r-test, and F-test methods, and this research analyzes data from a population consisting of 83 employees. The results of the analysis show that the two independent variables, namely work discipline and providing incentives, simultaneously affect employee performance, while the rest are influenced by other factors that were not studied. Simultaneous tests reveal that both work discipline and incentives have a significant influence on employee performance with the calculated F value and significance level. However, based on the t-test, only work discipline was proven to have a significant effect on employee performance, while providing incentives did not show a significant effect. The managerial implication that can be taken is the importance of increasing work discipline as a significant factor in improving employee performance. The research results show that work discipline has a positive and significant influence on employee performance while providing incentives does not have a significant impact. Therefore, the management of PT. TOA Galva Industries must prioritize strengthening work discipline through strict supervision and consistent application of rules.